Java Instituut: Implementasi Intelektual Lokal dan Kolonial dalam Memajukan Kebudayaan Sunda 1921-1941 - Fauzi, Kiki Rizki; Wiyanarti, Erlina; Yulianti, Iing (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
The Dutch have studied indigenous society and culture since the 19th century. The Dutch researched the Javanese language, Malay, and ancient manuscripts through its scholars. The lack of indigenous participation in studying and researching their knowledge system and culture allowed the Dutch to instill power in the field of culture. In the early 20th century, the study of society and culture began to involve the natives, marked by the establishment of the Java Institute. Java Instituut’s openness to cultural advancement efforts can be seen in cooperation between local and colonial intellectuals. This research aims to analyze the role of Java Instituut in advancing Sundanese culture from 1921 to 1941. The research method used is the historical method, which consists of the stages of heuristics, source criticism, interpretation, and historiography. Through this research, it can be seen the strategic steps of Java Instituut in advancing Sundanese culture, namely: 1) Promoting Sundanese tunil (opera); 2) Publishing Sundanese magazines; 3) Organizing Sundanese language congresses; and 4) Establishing arts and crafts schools.